DIGITALIZATION TRAINING AND GUIDANCE OF HALAL PRODUCT CERTIFICATION BASED ON LOCAL WISDOM AS AN EFFORT IMPROVING THE COMPETITIVENESS OF UMKM ANCHOR CHIPS IN DISTRICT SOUTH SIBOLGA - Dewi Sundari; Rodi Syafrizal; Liza Widya Hasyim; Bestari Endayana; Muallif Masyhuri; Irwansyah Putra; Rangga Salam (RADJA PUBLIKA, 2024)
implementation of this PKM is designed with offline meetings and direct field visits in order to reach a wider audience. Moreover, the theme raised is related to Digital Halal Certification and Halal Labels for MSME products. The selection of the South Sibolga sub-district area, in addition to being based on an agreement to provide assistance with the Sibolga City Ministry of Religion, is also based on the still less than optimal registration of digital halal certification and halal labels on MSME products in order to increase competitiveness outside the region and abroad, especially still not being able to compete with other regional products. The Community Service Program in partnership with the Ministry of Manpower, Trade Office, South Sibolga Traffic, is held offline and directly in the field. More specifically to independent small and medium business actors under the guidance of the Ministry of Home Affairs and Academics to the Creative Digital Halal Certification Registration Training Based on Local Wisdom to Increase the Competitiveness of MSME Products, Ministry of Religion of Sibolga City and the Perdanaganan Service, Sibolga City in 2023-2024. The implementation is carried out by delivering materials, discussions, to simulations of registration of Digital Halal Certificates packaged from local Sibolga culture adjusted to the products of each MSME. In its implementation, we found it difficult to simulate directly and see MSME products as participants directly. The implementation that we made in the Community Service program for independent small and medium enterprises (MSMEs) was fairly successful because it received a huge response from the MSME community.